Waste Management the Low-Cost Apartment Building, District of Baleendah Bandung 2018 - Maulani, Qurnia; Fatimah, Wulan Nur (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: Bandung was one of the areas that had not applied a good waste management yet. From 1,440 tons/day waste produced around 320 tons were managed. The effects of untreated waste were carrying the vector of disease, aesthetic decrease, environmental quality, and flood. The aim of this research was to identify the condition of waste management in Rusunawa Balaendah in 2018. Method: The research used observational method with cross sectional design. The object of this research was families who lived in Rusunawa Balaeendah with 60 respondents were obtained with sampling random area tehcnique. Observation variables were sorting, storing, collecting, and the amount of waste generation. This research used direct measurement method to calculated the waste generation during 8 days in May 15 to 21 2018 according to SNI No. 19-3964-1994. Method for collected the data used interview and field observation. The data was presented by table frequency distribution and chart to analyzed the result of the observation. Result and Discussion: The result of this research was shown that respondents who had good waste management were 3%, the storage phase for the ownership of trash that had not requirements yet were 70%, and garbage that was not in TPS was 97%. The amount of waste generation was 0.356kg/person/day. The level of respondents' knowledges about it was 45% which was on adequate category and the behaviour was 96,6% which was on deficient category. Conclusion: The result of this research was to know that waste management in Rusunawa Balaeendah was not appropriate with the provision. Based on the research, the suggestion is to build a garbage dump that has 3R method of waste management and to collaborate with DKRTH for the transfer of residual waste.